Real-time garments defects detection at the sewing phase to optimize waste cost using YOLOv7, YOLOv7x, YOLOv7-w6 and Pytorch - Uddin, Md. Minhaz; Foysal, Sadi Mahmud; Rahman, Sadia; Risti, Nushara Tazrin; Sarmin, Sanzeda Akter (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.